Design and Development of a Portable Water Ionizer Based on the Internet of Things (IoT) with Battery Utilization and Portability Capability - Usman, Uke Kurniawan; Mitto, Antonio Abhinyano (Department of Informatics Universitas Islam Indonesia, 2024)
A portable water ionizer has been successfully developed as an innovative solution to provide healthy and high-quality water conveniently while traveling. The device utilizes six 18650 lithium-ion batteries connected in series with a maximum voltage of 25.2 Volt DC and a current capacity of 1500 mAh as the main power source for the water electrolysis process. Additionally, two 8.4 Volt DC batteries are used to power the microcontroller and sensors. The total power required for the entire device is approximately 13.274 Watt, allowing the device to operate for approximately 3 hours. Portability testing was conducted through a questionnaire involving the participation of 22 respondents. The majority of respondents, 15 out of 22, stated that the device is easy to carry while traveling and demonstrates good portability. This can be attributed to its compact dimensions (17 cm x 13 cm x 37 cm) and relatively light weight (1.5 kg in dry condition and 2.5 kg in water-filled condition). Another advantage of the device is its ability to operate without a connection to household electricity, making it a practical and portable option for users to carry while traveling. The positive results of the portability testing confirm that the portable water ionizer successfully meets the desired portability standards. With its easy-to-carry design, the device can be an efficient and convenient solution for individuals who travel frequently and prioritize the quality of the water they consume.